KAJIAN TERHADAP IMPLEMENTASI KEBIJAKAN PERLINDUNGAN HUKUM BAGI ANAK KORBAN KEKERASAN SEKSUAL DI DALAM KELUARGA DI INDONESIA - Adriani Adnani (Ensiklopedia Education Review, 2023)
The family has a very important role in the development of children's personality and education which later becomes one of the determining factors in the child's life. However, many phenomena occur both in the world and in Indonesia, there are still many children who get sexual violence behavior precisely from the family environment. The very sad fact is that there are children who suffer from sexual violence that occurs in the family environment. Sexual abuse in childhood is often perpetrated by a family member or someone who is known and trusted by the family. The results showed that Indonesia already has a legal policy to handle cases of sexual violence against children, especially those that occur in the family environment. These laws and regulations have been implemented quite well, although until now they have not been able to provide a deterrent effect to the perpetrators.Keywords: policy implementation, legal protection, sexual violence